Reconstruction Politics in a Deep South State : Alabama, 1865-1874 - Rogers, William Warren, Jr., 1955- (Book collections on Project MUSE., 2021)
"Following the end of the Civil War, white Southerners were forced to concede equal rights to former slaves, ushering in a new and ruthless brand of politics. Suddenly, the status and place of some four million ex-slaves dominated the national and regional political dialogue. The Republican Party established itself quickly and powerfully with the participation of a newly freed constituency, firmly aligned against the Democratic Party that had long dictated the governance of the state. Well-heeled planters, merchants, and bankers, joined by yeoman farmers, gravitated strongly to the Democratic Party and its unabashedly white supremacist measures, staging a counterrevolution. The ensuing power struggle in the birthplace of the Confederacy is at the heart of Reconstruction Politics in a Deep South State: Alabama, 1865-1874"--